2021
DOI: 10.3390/ijerph18094902
|View full text |Cite
|
Sign up to set email alerts
|

A Model of the Effects of Parental Illness on Youth Adjustment and Family Functioning: The Moderating Effects of Psychological Flexibility on Youth Caregiving and Stress

Abstract: Parental chronic illness may adversely impact youth and family functioning. This study examined a moderated mediation model of the effects of parental illness on youth and family functioning derived from the Family Ecology Framework. Consistent with this model, we predicted that youth caregiving and stress would serially mediate the adverse impacts of parental illness on youth adjustment and family functioning and that psychological flexibility would moderate these mediational mechanisms. A total of 387 youth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 67 publications
3
21
0
Order By: Relevance
“…This causal link is in line with the family ecology model (Pederson & Revenson, 2005). The model proposes that parental health problems impact youth's stress experiences over family role redistributions (including changes in young people's roles and responsibilities) and was supported by previous research (e.g., Landi et al, 2021).…”
Section: Discussionsupporting
confidence: 73%
“…This causal link is in line with the family ecology model (Pederson & Revenson, 2005). The model proposes that parental health problems impact youth's stress experiences over family role redistributions (including changes in young people's roles and responsibilities) and was supported by previous research (e.g., Landi et al, 2021).…”
Section: Discussionsupporting
confidence: 73%
“…Understanding this can assist in identifying at-risk AYAs with higher perception of parental illness unpredictability and unmet needs, and providing tailored interventions to improve their psychosocial adjustment to parental cancer. These interventions could include the following: (1) increasing AYAs understanding of, and active involvement in, their parents' cancer treatment and care through psychoeducation and attending medical appointments with their ill parent [48]; (2) encouraging discussion about cancer within the family and the participation of AYAs in peer recreation/ therapeutic camps which provide an opportunity for psychosocial support, skill development, and time out from the daily stresses of living with a parent affected by cancer [49]; and (3) using acceptance and commitment therapy based therapeutic approaches that facilitate having a different relationship with the realities of uncertainty and unpredictability while focusing the young person's energy on living their life in line with their values [42,50].…”
Section: Discussionmentioning
confidence: 99%
“…1 As expected, illness unpredictability was positively related to unmet needs in AYAs. The total model accounted for 15% of the variance in offspring unmet needs which represents a medium effect size [42].…”
Section: Levels Of Unmet Needs and Ayas Psychosocial Adjustment And The Relationship Between Demographic And Cancer Variables On Level Ofmentioning
confidence: 99%
“…Adolescents whose parents are chronically ill are significantly more likely to show internalizing problems (i.e., anxious, depressed, and withdrawn behaviors and somatic complaints) than other children (5,8,(14)(15)(16)(17)(18). While in the general population, adolescent females show more internalizing symptoms than males (19)(20)(21), a meta-analysis found that sex differences regarding internalizing problems in children with parental chronic illnesses are negligible (5).…”
Section: Introductionmentioning
confidence: 97%
“…Knowledge of the longitudinal effects of parental chronic illness is scarce and inconsistent; however, some studies have indicated that the increased risk of internalizing symptoms persists into adulthood (14,22). Hence, research into potential mediating and moderating factors in the pathways between parental chronic illness and internalizing symptoms in adolescents as they transition into adulthood is essential for developing effective interventions for families experiencing parental illness (12,18,23).…”
Section: Introductionmentioning
confidence: 99%